The role of pudendal nerve block in hemorrhoid surgery: a systematic review and meta-analysis of double-blind randomized controlled trials - Xia, Shijun; Luo, Lidan; Wu, Wenjiang; Lu, Kaiyuan; Jiang, Tao; Li, Yue (Frontiers in Medicine, 2023)
Background: Pudendal nerve block (PNB) is a commonly used anesthesia method that has been widely used in postoperative analgesia for hemorrhoids in recent years. Therefore, we conducted a systematic review and meta-analysis of doubleblind randomized controlled trials (RCTs) to analyze the effectiveness of PNB in postoperative analgesia for hemorrhoids.Relevant data and studies published from inception until August 14, 2023, were retrieved from PubMed, Embase, and Web of Science to evaluate the beneficial effects of PNB for analgesia following hemorrhoidectomy.Results: This meta-analysis included 6 double-blind RCTs comprising 501 patients. We evaluated the function of PNB in improving outcomes of postoperative analgesia of hemorrhoids. Visual analogue scale (VAS) scores on postoperative within 6h (MD, −3.04; 95% CI, −4.13 to −1.95; P<0.0001), 12h (MD, −3.14; 95% CI, −3.87 to −2.40; P<0.0001), and 24h(MD, −2.25; 95% CI, −2.95 to −1.55; P<0.0001) were enhanced by the application of PNB, but not in 48h(MD, −2.54; 95% CI, −5.29 to 0.20; P＝0.07).PNB could effectively relieve postoperative pain of hemorrhoids. However, our results still need to be confirmed by multi-center clinical studies.